A CROSS-SECTIONAL STUDY TO ASSESS SELF-MEDICATION FOR VARIOUS CONDITIONS AMONG MEDICAL, PARAMEDICAL, AND NON-MEDICAL STUDENTS - MISHRA, POOJA SOLANKI; MORE, SAPNA; GUPTA, KAMAYANI; RASTOGI, DEEPTI; VIGNAN, NARLAPATI (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The objectives of the study are to assess the knowledge about self-medication and factors influencing the use of self-medication among 2nd year medical, paramedical, and non-medical students. Methods: A cross-sectional, multicenter study was conducted among 520 students of medical, physiotherapy, nursing, and engineering courses. Students were given a pre-structured questionnaire in e form/physical forms. The responses were collected and analyzed using descriptive statistics. Results: It was found that 63% of students followed self-medication, among which 41% took medication from a chemist. Analgesic and antipyretic (31.8%) followed by cough and cold (23%) medication were the most common group for self-medication. Conclusion: Self-medication is seen more commonly in medical students, especially the hosteller group. The most common reason for self-medication is the easy availability of drugs and the absence of strict regulations.